SELFIE AS PROMPT FOR NARRATIVE WRITING - Pek, Lim Seong; Mee, Rita Wong Mee; Abdul Ghani, Khatipah (PROJECT (Professional Journal of English Education), 2020)
The evolution of pictures has brought changes to communication in the current time. From smoke signal to smartphones as a medium of communication, has enabled people to keep in touch with one another easier. The development of technology produces internet which is essential to every humankind around the world. With the help of internet, people could now upload pictures, especially Selfies, and post them on social media for others to view and respond to them. Through this medium of sharing over the social media, Selfies are used to deliver messages to facilitate communication better by saying their mind out on what they see and think. Hence, this study was carried out to examine the effects of Selfie as prompt to generate ideas for narrative writing among undergraduates in a local higher education in Malaysia. The findings had shown significant improvement in undergraduates’ writing in term of ideas coherency and text length. It was observed that undergraduates were able to narrate their experiences and stories related to their own Selfies as compared to non-pictorial writing. As a whole, the use of Selfie as prompt had improved undergraduates’ writing ability as well as their level of confidence in language expression.